PENERAPAN STRATEGI PEMBELAJARAN AKTIF PLANTED QUESTIONS UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI MIPA SMAN 1 KAMPAR - Suryani, Melva; ', Susilawati; Rery, R. Usman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research on application of active learning strategy planted questions to improve learning achievement of learners on the subject of solubility and solubility results in class XI MIPA SMAN 1 Kampar on April. Form of research is experimental research with pretest-posttest design. The sample consist of two class, namely class XI MIPA 1 as the experimental class and class XI MIPA 3 as control class which randomly selected after had tested normality and homogeneity. Experimental class is a class that implemented of active learning strategy planted questions while the control class used discussion information methods. Data analysis technique used is the t-test. Based on the results of the final data processing using t-test formula obtained tcount > ttable (4,615 > 1,669) means the application of active learning strategy planted questions can improve student achievement on the subject of solubility and solubility results in class XI MIPA SMAN 1 Kampar, with an increasing percentage of 23,851% .Keywords : Active learning strategy planted questions, Learning Achievement and solubility and solubility.